Evolution of managerial problems from the perspective of management science - Szarucki, Marek (Business: Theory and Practice, 2015)
Managerial problems and the process of their solving play an important role both in the theory of management science and practice of organisations’ functioning. There is a gap in the literature related to the evolution of management problems in the context of the methodological approaches to solve them. The main goal of this paper was to analyse the evolution of the managerial problems from the perspective of management science and to present dominant methodological approaches for problem solving. Based on the extensive literature analysis in the discipline of management science, the evolution of the managerial problems was described with relation to the sixteen streams of management science. The author reviewed the selected classifications of the management theory as well as proposed his own perspective, which took into account managerial problems and their evolution over time. Moreover, there was presented an attempt to depict sources of management problems from the historical perspective within the methodological approaches of management science. Despite the broad view on management problems presented in this paper, such perspective gives a good ground for developing new more specific problem classifications, addressing different facets of managerial problems.